Adherence to guidelines when evaluating fitness-to-drive in the elderly: a practice review of Swiss physicians (Swiss Medical Weekly, 2018)
OBJECTIVE We aimed to explore the extent to which general practitioners (GPs) in Western Switzerland adhere to Swiss recommendations when assessing fitness-to-drive in the elderly. METHODS A random sample of 500 GPs practicing in Vaud, Neuchatel and Jura, and all GPs certified to conduct fitness-to-drive assessments in Geneva (“experts”, n = 69) were invited to participate. They were asked how often they performed twenty procedures (recommended in Swiss guidelines developed by experts in traffic medicine) when assessing older drivers during the previous year, scored on a five-point Likert scale ranging from “never” to “always performed”. The GPs were considered to be adhering to the recommended procedure if they performed it often or always. We computed the proportion of GPs adhering to each procedure, and compared GPs with or without specialised expertise. RESULTS A total of 268 GPs completed the questionnaire (participation rate 47%). The most frequently reported procedures were asking for current medication (96%), cardiovascular (94%) and neurological diseases (91%), and screening for visual acuity impairment (93%), whereas the least frequently reported procedures were screening for cognitive impairment in drivers aged between 70 and 80 years (44%) and for mood disorder (31%), asking for a history of driving license withdrawal (38%), and interviewing close relatives (10%). Six procedures were statistically significantly more frequently performed by the experts than by the other GPs. In general, GPs reported using validated tools, except when screening for at-risk drinking and mood disorder (tools used by 26 and 28%, respectively). CONCLUSIONS Many Swiss GPs seem not to systematically follow the current Swiss recommendations. Although several important procedures appear to routinely be part of older drivers’ assessment, others are infrequently performed. Further research should identify how GPs select the recommended items to which they adhere and those they never apply, and how to facilitate the use of recommended procedures to help them decide if a person is fit, unfit or requiring further evaluation.